5x+5x+1+5x+2=31tìm x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = (5\(x\) + 1)2 + (5\(x\) - 1)2 - 2.( 5\(x\) +1).(5\(x\) - 1) tại \(x\) = 1
Thay \(x\) = 1 vào A ta có:
A = (5.1 + 1)2 + (5.1 - 1)2 - 2.(5.1 + 1).(5.1 - 1)
A = 62 + 42 - 2.6.4
A = 36 + 16 - 48
A = 52 - 48
A = 4
(x2-5x+1)2+2(5x-1)(x2-5x+1)+(5x-1)2
= [(x2-5x+1)+(5x-1)]2
= (x2-5x+1+5x-1)2
= (x2)2
= x4
Tại \(x=4\)thì:
\(x^5-5x^4+5x^3-5x^2+5x-1\)
= \(x^5-\left(x+1\right)x^4+\left(x+1\right)x^3-\left(x+1\right)x^2+\left(x+1\right)x-1\)
= \(x^5-x^4-x^4+x^4+x^3-x^3-x^2+x^2+x-1\)
= \(3\)
(x2 - 5x + 1)2 + 2(5x - 1)(x2 - 5x + 1) + (5x - 1)2 = (x2 - 5x + 1 + 5x - 1)2 = (x2)2 = x4
Lời giải:
Tại $x=4$ thì:
\(A=5(x^5-x^4+x^3-x^2+x-1)-1\)
\(=(x+1)(x^5-x^4+x^3-x^2+x-1)-1=x^6+1-1=x^6\)
\(=4^6=4096\)
5x+5x+1+5x+2=31
5x + 5x + 5x = 31 - 2 - 1
15x = 28
x= 28/15